Study on practices/knowledge and recepies of traditional healers of treatment of Jaundice in Kathmandu valley - Koirala, Dr. Rishi Ram; Khaniya, Bhupendra Nirajan (2013)
Criteria for sample selection were simple - age, experience and profession of the healers. Emphasis was given to the varieties of method of treatment rather than the number of traditional healers for the research. So, only twenty traditional healers renowned in Kathmandu, Lalitpur and Bhaktapur districts were selected and made discussion in detail directly with them regarding the disease.